Do exports and innovation matter for the demand of skilled labor?. Issue 1 (2nd January 2021) - Aboushady, Nora; Zaki, Chahir
ABSTRACT: The objective of the paper is to examine the impact of exports and innovation on the demand for skilled labor in the Middle East and North Africa (MENA) region. In this matter, we contribute to the existing literature in several ways. First, we examine the connection between exports and skill bias through several innovation and technology adoption indicators, which we divide into core product-related innovation and innovation in auxiliary services. Second, we differentiate between the effect of innovation on skilled blue-collar (production workers) vs. white collar (non-production) workers. We also run the regressions for the manufacturing sector and the services sector separately. Third, we test this relationship for eight MENA countries, using firm-level data from the World Bank Enterprise Survey (2013). Our results suggest a positive and significant impact of the extensive trade margin on innovation and technology adoption, while trade at the intensive margin is insignificant. Furthermore, demand for skilled workers by firms in the MENA region is likely to be higher for production workers than that for non-production ones. This demand is particularly high when a firm adopts a new product, a new production method or spends on research and development, rather than in the case of spending on auxiliary services. At the sector level, the impact of innovation on the demand for skilled labor is positive and significant in the manufacturing sector.